I.) (5x+3)/4-(2x-4)/3=5
Clear fractions:
3·((5x+3)/4)=15x+9
4·((2x-4)/3)=8x-16
15x+9-(8x-16)=5
15x+9-8x+16=5
Combine like terms:
7x+25=5
7x=-20
x=-20/7
II.) (3/11)·(5/6)-(9/12)·(4/3)+(5/13)·(6/15)
Remember PEMDAS
So first multiply:
3/11·5/6=15/66
9/12·4/3=3/3·1/1=3/3=1
5/13·6/15=1/13·6/3=6/39=2/13
(15/66)-1+(2/13)
Combine:
15/66-1/1=15/66-66/66=-51/66
-51/66+2/3=-51/66+44/66=-7/66
Answer: -7/66 :)
It is an acute triangle because none of its angles are equal to (right) or above (obtuse) 90 degrees.
A=LW, we are told that the dimensions are 42 and 48 so:
A=42*48
A=2016in^2
Answer:
C
Step-by-step explanation:
over the interval [-1,1], f(x) is greater than 0